2016
DOI: 10.1111/jocn.13185
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from acute to primary health care nursing: an integrative review of the literature

Abstract: Aims and objectives This paper seeks to explore the transition experiences of acute care nurses entering employment in primary health care settings. Background Internationally the provision of care in primary health care settings is increasing. Nurses are moving from acute care settings to meet the growing demand for a primary health care workforce. While there is significant research relating to new graduate transition experiences, little is known about the transition experience from acute care into primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…As reported by Ashley et al. () in their review of transition to primary health care employment, the limited research is in stark contrast to the large body of literature published around the transition of new graduates into nursing practice (Cowin & Hengstberger‐Sims, ; Rush, Adamack, Gordon, Lilly, & Janke, ; Scott, Keehner Engelke, & Swanson, ). While common themes emerged from this review, the limited available literature highlights the need for further research to better understand the transition process and support workforce planning across the spectrum of health care areas.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As reported by Ashley et al. () in their review of transition to primary health care employment, the limited research is in stark contrast to the large body of literature published around the transition of new graduates into nursing practice (Cowin & Hengstberger‐Sims, ; Rush, Adamack, Gordon, Lilly, & Janke, ; Scott, Keehner Engelke, & Swanson, ). While common themes emerged from this review, the limited available literature highlights the need for further research to better understand the transition process and support workforce planning across the spectrum of health care areas.…”
Section: Discussionmentioning
confidence: 95%
“…While current theories of transition for newly qualified nurses outline specific process and its outcomes from such experiences (Duchscher, ), it is unclear whether such theories can be applied to experienced registered nurses. Furthermore, a recent literature review regarding registered nurse transition to primary health care (Ashley et al., ) found that successful transitions was associated with individual expectations, personal characteristics and organisational support and that understanding such experience during transition could optimise retention and enhance the nurses experiences. This integrative review will build on existing knowledge by critically synthesising what is currently known about the experiences of registered nurses transitioning into new clinical areas and identify considerations for research, policy and practice.…”
Section: Introductionmentioning
confidence: 99%
“…The experience of transition has been described in the literature as being personally and professionally challenging (Ashley, Halcomb, & Brown, ) (Banner & Johnston, ; Currie, Flinn, & Martin, ). This study has provided new data to explore the work satisfaction of experienced nurses new to PHC and their future career intentions.…”
Section: Discussionmentioning
confidence: 99%
“…The process of transitioning has been reported as stressful, and associated with a lack of confidence, role ambiguity and role conflict as the requirements of the new role become clear (Kramer, McGuire, Halfer, Brewer, & Schmalenberg, ; Parker, Giles, Lantry, & McMillan, ). These phases may be followed by periods of readjustment as workers “unfreeze” from the old role and acquire the skills and confidence needed to fulfil their new role (Ashley et al, , Ashforth, ; Holt, ). The association between these phases of transition and the impact they may have on job satisfaction, patient/client safety and retention in the workforce have not been widely researched in the PHC sector (Ashley et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These phases may be followed by periods of readjustment as workers “unfreeze” from the old role and acquire the skills and confidence needed to fulfil their new role (Ashley et al, , Ashforth, ; Holt, ). The association between these phases of transition and the impact they may have on job satisfaction, patient/client safety and retention in the workforce have not been widely researched in the PHC sector (Ashley et al, ). However, evidence from other sources, in particular new graduate nurses entering the workforce, suggests that negative transitioning experiences have been associated with increased staff turnover (Parker et al., ; Yeh & Yu, ) and patient safety concerns (Gaynor, Gallasch, Yorkston, Stewart, & Turner, ; Murray‐Parahi, DiGiacomo, Jackson, & Davidson, ; Rush, Adamack, Gordon, Lilly, & Janke, ).…”
Section: Introductionmentioning
confidence: 99%